Analyst Hype in IPOs: Explaining the Popularity of Bookbuilding - Degeorge, François; Derrien, François; Womack, Kent L. (Review of Financial Studies, 2007)
The bookbuilding IPO procedure has captured significant market share from auction alternatives recently, despite the significantly lower costs related to the auction mechanism. In France, where both mechanisms were used in the 1990s, the ostensible advantages of bookbuilding were advertising-related benefits. Book-built issues were more likely to be followed and positively recommended by lead underwriters. Even nonunderwriters' analysts promote book-built issues more in order to curry favor with the IPO underwriter for allocations of future deals. Yet we do not observe valuation or post-IPO return differentials that suggest these types of promotion have any value to the issuing firm.